Experimental study of beam to concrete-filled elliptical steel tubular column connections. (October 2015) - Yang, J.; Sheehan, T.; Dai, X.H.; Lam, D.
Abstract: This paper investigated the rotation behavior of simply bolted I-beam to concrete-filled elliptical steel tubular (CFEST) column connections experimentally. Ten different joint assemblies were tested to failure, with a constant axial compressive load applied to the column and upwards concentrated loads at the beam ends. All of the steel tubes were hot-finished and had a cross-sectional aspect ratio of 2. The orientation of the column and the arrangement of the stiffening plates were taken into consideration. Moment versus rotation relationships and failure modes were compared for each joint, highlighting the benefits of using core concrete and stiffeners in these connections. Highlights: Beam to elliptical hollow section (EHS) column connections were tested in bending. Different column orientations with stiffening/through plates were compared. Both hollow and concrete-filled EHS joints were employed. Moment–rotation relationships were obtained for each joint type. The benefits of concrete infill and stiffeners for these joints were highlighted.